QL1604 combined with bevacizumab as an innovative first-line treatment for HCC patient with extensive metastasis who showed remarkable effect: a case report - Wan, Yanzhi; Tan, Keqin; Zhu, Hong (Frontiers in Pharmacology, 2024)
Abstract: Hepatocellular carcinoma (HCC) is a common and highly malignant tumor with poor outcomes, especially when it metastasizes. In this report, we present the case of a 64-year-old male patient diagnosed with recurrence and multiple metastases of HCC 7 years after surgery. As the tumor invaded the spinal canal and pressed on the spinal cord, the patient experienced paralysis in the lower limbs. After undergoing surgical resection for spinal decompression, the patient chose an innovative regimen: QL1604 200 mg every three weeks plus bevacizumab 675 mg every three weeks as first-line treatment. From July 2022 to February 2024, the patient has regularly received the treatment. During the treatment, the paralysis symptoms of the patient gradually improved, and the motor function of the lower limbs completely returned to normal. When re-evaluated his spinal cord injury, the Frankel grade of the patient was downgraded from C to E. The tumor shrank to reach a state of PR and lasted for one and a half years. QL1604 combined with bevacizumab demonstrated excellent efficacy and minimal side effects in this patient. This new combined therapy holds potential as a first-line treatment strategy.